TQM Implementation in Character Education: Lessons Learned from Pesantren Gontor - Ahmad Saifulloh; Jia Ying Neoh (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
Due to its significance, character education implementation at Indonesian educational institutions including the Indonesian Islamic Boarding School (pesantren) is compulsory. However, the quality of its implementation within pesantren needs to be developed. This research was conducted to investigate the implementation of Total Quality Management (TQM) in the character education process as an endeavour to create Indonesian good citizens. To achieve the research objectives, a qualitative case study design at PesantrenGontor was employed. The research found that the process of character education at this pesantren is based on the core values of Gontor. There are some core characters inculcated at Gontor comprising sincerity, simplicity, self-reliance, care, freedom, religiousness, tolerance, discipline, and responsibility. Those characters are inculcated through the dynamic totality of campus life which contains a wide range of activities aimed at creating good citizens for Indonesia. The methods of character education are role model, creating a conducive milieu, directing, giving assignments, habituation, instruction, and training. Those methods are underpinned by the implementation of the basic concept of TQM that emphasises customer satisfaction which is limited by Gontor values. Based on the research findings, pesantren-based character education which is underpinned by TQM could be adopted by other models of educational institutions.